An innovative method establishment for a green shipyard concept - Bilgili, L.; Celebi, U. B. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2013)
Shipbuilding industry is known as one of the hardest metal industry with several chemicals and hazardous material. Most of the production processes such as welding, painting, blasting and fiberglass production have direct impact on workers' health. There are several wastes and pollutants being released during shipbuilding and ship repairing processes. The volume of these wastes and pollutants create a huge amount with major risk on environmental and ecological point of interest. The effect of shipyard on environment and human health can be reduced with technological improvements on shipbuilding industries. The inputs of these processes are various types of products and raw material such as primarily steel and other metals, paints and solvents, blasting abrasives, and machine and cutting oils with an outcome of different forms (solid, liquid, and gaseous) of wastes and pollutants as Volatile Organic Compounds (VOCs), Particulates (PM), waste solvents, oils and resins, metal bearing sludge and wastewater, waste paint, waste paint chips and sent abrasives. Life Cycle Assessment (LCA) is one of the most innovative and effective methods to minimize and initialize the harmful emissions caused by manufacturing and operation. LCA is also aims to minimize the energy consumption. For ship production phase is a long-term and emission-produced stage in a ship's life cycle, LCA method is used to manage the logistics and production process to provide time efficiency and besides, the method is used to reduce the emissions and discharges. In this paper, LCA method is explained and a new LCA method is established for a green shipyard.
Keywords: Engineering; Environmental Sciences & Ecology; Materials Science